2020
DOI: 10.5194/gmd-13-4663-2020
|View full text |Cite
|
Sign up to set email alerts
|

Optimality-based non-Redfield plankton–ecosystem model (OPEM v1.1) in UVic-ESCM 2.9 – Part 1: Implementation and model behaviour

Abstract: Abstract. Uncertainties in projections of marine biogeochemistry from Earth system models (ESMs) are associated to a large degree with the imperfect representation of the marine plankton ecosystem, in particular the physiology of primary and secondary producers. Here, we describe the implementation of an optimality-based plankton–ecosystem model (OPEM) version 1.1 with variable carbon : nitrogen : phosphorus (C:N:P) stoichiometry in the University of Victoria ESM (UVic; Eby et al., 2009; Weaver et al., 2001) a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 78 publications
0
25
0
Order By: Relevance
“…Temperature dependence was added by Arteaga et al (2014) following the simple logarithmic temperature dependence on maximum nutrient uptake rate following (Eppley, 1972). (Chien et al, 2020;Pahlow et al, 2020). However, as we are not describing any results in this paper, we will only mention here that there is an option to calculate C:N:P using this stoichiometry model in MESMO 3.…”
Section: Optimality-based Model Of Stoichiometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature dependence was added by Arteaga et al (2014) following the simple logarithmic temperature dependence on maximum nutrient uptake rate following (Eppley, 1972). (Chien et al, 2020;Pahlow et al, 2020). However, as we are not describing any results in this paper, we will only mention here that there is an option to calculate C:N:P using this stoichiometry model in MESMO 3.…”
Section: Optimality-based Model Of Stoichiometrymentioning
confidence: 99%
“…The full description of the optimality-based stoichiometry model and its parameter calibration are presented specifically for the UVic model elsewhere (Chien et al, 2020;Pahlow et al, 2020).…”
Section: Optimality-based Model Of Stoichiometrymentioning
confidence: 99%
“…Thus, it can be concluded that IA provides improved realism over the computationally equivalent FS approach. For simulating a few years of the dynamics of the single phytoplankton group in a 1D setup as we did here, differences in computational costs relative to the fully dynamic variant are nearly negligible, but for simulating decades/centuries or millennia in a 3D setup (e.g., as in Pahlow et al, 2020), and/or when multiple clones/types are considered (e.g., 350 in Dutkiewicz et al, 2020), differences in computational costs can indeed be substantial.…”
Section: Modelling Variable Phytoplankton Compositionmentioning
confidence: 91%
“…Furthermore, given its mechanistic basis, this approach can be expected to reproduce biological feedbacks more realistically (Flynn et al, 2015), and thereby improve the generality and portability of models (Anugerahanti et al, in prep.). Recent applications of these models in 3D setups with realistic forcings (Kerimoglu et al, 2017;Pahlow et al, 2020) have indicated that accounting for acclimation enhances the ability of models to reproduce field observations. Moreover, a consistent representation of phytoplankton composition allows identification of potential alterations in trophic transfer efficiencies as mediated by changes in food quality of prey in response to environmental change (Kerimoglu et al, 2018;Kwiatkowski et al, 2018).…”
Section: Modelling Variable Phytoplankton Compositionmentioning
confidence: 99%
“…implemented in global ocean biogeochemical models, such as the Pelagic Interactions Scheme for Carbon and Ecosystem Studies (PISCES) (Kwiatkowski et al, 2018(Kwiatkowski et al, , 2019 and the University of Victoria Earth System Model (UVIC) (Chien et al, 2020;Pahlow et al, 2020). However, as we are not describing any results in this paper, we will only mention here that there is an option to calculate C:N:P using this stoichiometry model in MESMO 3.…”
Section: Different Versions Of This Optimality-based Model Have Previously Been Successfullymentioning
confidence: 99%